Investigation on the Growth, Linear and Non-Linear Optical, Thermal and Photoconductivity Properties of L-Tartaric Acid-Nicotinamide Crystal - Ramesh Kumar, P.; Kumararaman, S.; Sagayaraj, P. (Asian Journal of Chemistry, 2010)
Organic materials which exhibit very large second order non-linearity with high laser damage threshold find application in the field of frequency conversion, image processing data storage, fiber optic communication etc., The present work deals with the growth of L-tartaric acidnicotinamide (LTN), an organic crystal with non-linear optical activity. The crystal has been grown by slow solvent evaporation technique and the growth conditions suitable for bulk size are optimized. The structural and morphological properties of the crystal are investigated using X-ray diffraction. The linear and non-linear optical properties of the L-tartaric acid-nicotinamide crystal are studied by FT-IR and, UV-vis-NIR spectroscopic techniques and Kurtz and Perry powder SHG test. The thermal, microhardness and photoconductivity studies are also carried out.